Molecular Mechanisms of Antipsychotic Drug-Induced Diabetes - Chen, Jiezhong; Huang, Xu-Feng; Shao, Renfu; Chen, Chen; Deng, Chao (Frontiers in Neuroscience, 2017)
Antipsychotic drugs (APDs) are widely prescribed to control various mental disorders. As mental disorders are chronic diseases, these drugs are often used over a life-time. However, APDs can cause serious glucometabolic side-effects including type 2 diabetes and hyperglycaemic emergency, leading to medication non-compliance. At present, there is no effective approach to overcome these side-effects. Understanding the mechanisms for APD-induced diabetes should be helpful in prevention and treatment of these side-effects of APDs and thus improve the clinical outcomes of APDs. In this review, the potential mechanisms for APD-induced diabetes are summarised so that novel approaches can be considered to relieve APD-induced diabetes. APD-induced diabetes could be mediated by multiple mechanisms: (1) APDs can inhibit the insulin signalling pathway in the target cells such as muscle cells, hepatocytes and adipocytes to cause insulin resistance; (2) APD-induced obesity can result in high levels of free fatty acids and inflammation, which can also cause insulin resistance. (3) APDs can cause direct damage to β-cells, leading to dysfunction and apoptosis of β-cells. A recent theory considers that both β-cell damage and insulin resistance are necessary factors for the development of diabetes. In high-fat diet-induced diabetes, the compensatory ability of β-cells is gradually damaged, while APDs cause direct β-cell damage, accounting for the severe form of APD-induced diabetes. Based on these mechanisms, effective prevention of APD-induced diabetes may need an integrated approach to combat various effects of APDs on multiple pathways.